2011
DOI: 10.1007/s10585-011-9372-1
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ is essential for the inhibition of B16BL6 melanoma lung metastasis in chronic alcohol drinking mice

Abstract: We previously found that chronic alcohol consumption (20% w/v in drinking water) that models the level consumed by human alcoholics, when administered to female C57BL/6 mice inhibits B16BL6 melanoma metastasis to the lung; however, the mechanism is not known. Chronic alcohol consumption increases IFN-γ producing NK, NKT, CD4+, and CD8+ T cells. To examine the impact of IFN-γ on metastasis, we inoculated B16BL6 melanoma cells i.v. into control and chronic alcohol drinking IFN-γ knockout (KO) mice. Knockout of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We previously reported that chronic alcohol consumption increases IFN-γ-producing memory T cells, NK cells and NKT cells in the non-melanoma injected mice [25, 28, 29, 34]. The percentage of IFN-γ-producing T cells in the alcohol-consuming mice continues to be elevated up to 11 days after s.c. melanoma inoculation as compared to water-drinking mice [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that chronic alcohol consumption increases IFN-γ-producing memory T cells, NK cells and NKT cells in the non-melanoma injected mice [25, 28, 29, 34]. The percentage of IFN-γ-producing T cells in the alcohol-consuming mice continues to be elevated up to 11 days after s.c. melanoma inoculation as compared to water-drinking mice [26].…”
Section: Resultsmentioning
confidence: 99%
“…We found that chronic alcohol consumption along with advancing growth of s.c. melanoma leads to inhibition in the expansion of memory and melanoma-specific CD8 + T cells, acceleration in the decay of Th1 cytokine producing CD8 + T cells [26], and compromised circulation of mature B cells [27]. Chronic alcohol consumption also increases invariant NKT (iNKT) cells and especially IFN-γ-producing iNKT cells [28] [29]. iNKT cells are specific T cells that recognize lipid antigens and produce a broad spectrum of cytokines upon activation [30].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of B16BL6 melanoma lung metastasis in mice chronically consuming alcohol was abrogated in IFN-γ knockout (KO) mice ( Fig. 18.1 ) [ 43 ]. This suggests that the anti-metastatic effect induced by chronic alcohol consumption is dependent on the IFN-γ signaling pathway and that multiple cell types are involved in this process.…”
Section: Chronic Alcohol Consumption Inhibits B16bl6 Melanoma Lung Mementioning
confidence: 89%
“…The anti-metastatic effect induced during alcohol consumption is maintained in γC knockout mice, which lack NK, B, and CD8 + T cells ( Fig. 18.1 ) [ 43 ]. While tumor metastasis is a complicated process, IFN-γ plays an important role in control of melanoma metastasis [ 44 ].…”
Section: Chronic Alcohol Consumption Inhibits B16bl6 Melanoma Lung Mementioning
confidence: 99%
“…Several epidemiologic studies presented controversial effects of alcohol consumption on cancer-associated outcomes, including survival rate and metastasis (5). An animal study showed chronic alcohol consumption accelerated melanoma metastasis into the lung by suppression of natural killer (NK) cells (6), whereas another study presented suppression of melanoma by alcohol intake via activating IFNg-producing immune cells (7).…”
Section: Introductionmentioning
confidence: 99%